Kebijakan Pengelolaan Lingkungan Pendidikan Pada Pembelajaran di Mts Al – Jumhuriyah - Nisa Miranda; Hanna Sholiha Mashar; Ayyu Purnama; Aldi Nasution; Wasiyem Wasiyem (Jurnal Ilmiah Wahana Pendidikan, 2023)
The policies applied by management in the learning environment are the most important thing in the learning process. Management of the learning environment itself is an activity related to facilities and infrastructure that connects student activities with the surrounding environment. Where students can carry out various activities, explore and be creative. Learning activities other than in class are very important, apart from not making children's mindset narrow, students must also be given learning in the form of an understanding of the wider environment. For example, in this study, the policy adopted by the teachers was to limit children's creative patterns by only doing learning in the classroom. However, when given the policy to carry out experiments outside the classroom, children understand learning more quickly